Our Lady of the Way Roman Catholic Church in Haines Junction, Yukon Territory - Campbell, Sandy (1987)
This church was opened in 1954. It is a repurposed quansite hut (long narrow, metal corrugated building) that was used by the American military while buiding the Alaska highway. It is located on Backe Street in Haines Junction, YT.